Solve the equation 3sinh(2x) = 13 - 3e^(2x), answering in the form 0.5ln(k). where k is an integer

We know that: sinh(2x) = 2sinh(x)cosh(x) , therefore the equation becomes 6sinh(x)cosh(x) = 13 - 3e2xWe also know that sinh(x) = 0.5*[ex-e-x] and that cosh(x) = 0.5*[ex+e-x], so the equation can be expanded into :
6/4[e2x-e-2x] = 13 - 3e2x3e2x -3e-2x = 26 - 6e2x
Rearrange and multiply by e2x to get a quadratic in e2x:9e4x - 26e2x - 3 = 0
Use Quadratic formula to find possible values for e2x.Since e2x must be greater than zero, only one answer is valid.Simply rearrange that answer to find the value of x.Answer: x = 0.5ln3

Related Further Mathematics A Level answers

All answers ▸

Sketch the locus of z on an Argand diagram if arg[(z-5)/(z-3)] = π/6


Show that the sum from 1 to n of 1/(2n+1)(2n-1) is equal to n/(2n+1) by Induction


How to integrate ln(x)?


The ODE mx'' + cx' + kx = 0 is used to model a damped mass-spring system, where m is the mass, c is the damping constant and k is the spring constant. Describe and explain the behaviour of the system for the cases: (a) c^2>4mk; (b) c^2=4mk; (c) c^2<4mk.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences